2019
DOI: 10.3390/molecules24112111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Diketopiperazines from Marine-Derived Streptomyces puniceus on the Isocitrate Lyase of Candida albicans

Abstract: The glyoxylate cycle is a sequence of anaplerotic reactions catalyzed by the key enzymes isocitrate lyase (ICL) and malate synthase, and plays an important role in the pathogenesis of microorganisms during infection. An icl-deletion mutant of Candida albicans exhibited reduced virulence in mice compared with the wild type. Five diketopiperazines, which are small and stable cyclic peptides, isolated from the marine-derived Streptomyces puniceus Act1085, were evaluated for their inhibitory effects on C. albicans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In a similar assay, compound 2 showed weak inhibition (IC 50 = 104.3 μM) of isocitrate lyase (ICL) derived from C. albicans . The IC 50 value of compound 2 is comparable to the previously reported diketopiperazine cyclo( l -Phe- l -Val) (IC 50 = 109.5 μM) isolated from marine-derived Streptomyces puniceus [22].…”
Section: Resultssupporting
confidence: 76%
“…In a similar assay, compound 2 showed weak inhibition (IC 50 = 104.3 μM) of isocitrate lyase (ICL) derived from C. albicans . The IC 50 value of compound 2 is comparable to the previously reported diketopiperazine cyclo( l -Phe- l -Val) (IC 50 = 109.5 μM) isolated from marine-derived Streptomyces puniceus [22].…”
Section: Resultssupporting
confidence: 76%
“…The antifungal activity of secoemestrin C ( 1 ), dethiosecoemestrin ( 2 ), emestrin ( 3 ), and emestrin B ( 4 ) was evaluated against C. albicans strains (SC5314, ATCC10231, ATCC10259, ATCC11006, and ATCC18804) using a previously documented procedure [ 33 ]. The growth of C. albicans was monitored in YNB broth with glucose or potassium acetate as the carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…Isocitrate lyase (ICL) and maltate synthase are the key enzymes involved in the Glyoxylate cycle. During host infection, pathogenic microorganisms such as Aspergillus fumigatus, Magnaporthe grisea, Burkholderia pseudomallei, Mycobacterium tuberculosis and C. albicans cause upregulation of the glyoxylate cycle [139,140]. In particular, the icl gene of C. albicans is strongly activated when cells are exposed to macrophages [137].…”
Section: Glyoxylate Cyclementioning
confidence: 99%
“…Research has shown that disruption of icl gene rendered C. albicans unable to utilise acetate, ethanol or oleic acid. It has also been found that ICL is crucial for the survival of C. albicans in response to macrophage engulfment [137][138][139].…”
Section: Glyoxylate Cyclementioning
confidence: 99%
See 1 more Smart Citation